Effect of fresh bed materials on alkali release and thermogravimetric behavior during straw gasification. (15th March 2023) - Ge, Yaxin; Ding, Saiman; Zhang, Wennan; Kong, Xiangrui; Engvall, Klas; Pettersson, Jan B.C.
Highlights: Online alkali measurement during gasification of straw and fresh bed material blends. The main elements in bed material migrate to the char surface and affect gasification. Dolomite significantly increases alkali release from straw during gasification. Si-containing materials reduce gasification reactivity and alkali release. Alumina reduces char gasification reactivity due to K-Al-Si ternary reactions. Abstract: Alkali-associated problems are key issues for the efficient use of straw that is available as a major renewable energy resource worldwide. The effects of six bed materials commonly used in fluidized bed reactors on straw pyrolysis and char gasification were evaluated using online monitoring of alkali release and thermogravimetric analysis. Scanning electron microscopy with energy dispersive spectroscopy was used to determine the elemental composition of the char surface. In the straw pyrolysis stage, alkali release is reduced by the addition of dolomite and silica due to alkali adsorption on the bed materials, and enhanced by the addition of alumina because of its high sodium content. In the char gasification stage, silica, sea sand, olivine, and ilmenite reduce the char reactivity and alkali release, which is attributed to transfer of Si and Ti from the bed materials to the char and reaction with alkali to form stable and catalytically inactive compounds. Alumina also reduces the char conversion rate by transfer of Al to the char and formation of K-Al-Si and Ca-Al-Si compounds, while alkali release from the straw and alumina blend remains high due to the high Na content in alumina. Dolomite initially appears to increase the char gasification reactivity, but the results are affected by conversion of volatile matter that deposited on the dolomite in the straw pyrolysis stage. Dolomite also significantly increases the alkali release, which is attributed to Ca reactions with aluminosilicate compounds that allow potassium to remain in volatile form. Fresh bed materials are concluded to have significant effects on straw conversion depending on their chemical composition, and the results can contribute to the understanding required for efficient use of straw in commercial applications of biomass thermochemical conversion.